Say no moor - Hunter, Maddy (Hunter, Maddy. Passport to peril mystery, 2018)
Hoping to reach an expanded clientele of senior travelers, Emily Miceli, travel agency owner and tour escort, offers discounted fares to a handful of bloggers in exchange for highlighting her group's tour of Cornwall, England. But when the quarrelsome host of their historic inn dies under suspicious circumstances, Emily worries that the bloggers' coverage of the situation will torpedo her travel agency.